Basic research for ultrasound-guided injection into skeletal muscle lesions in an experimental animal model - KiyomitsuFujimoto; TakashiKanamoto; ShunyaOtani; RyoMiyazaki; KosukeEbina; KenNakata (Bone & Joint Research)
Aims: Ultrasound-guided injection techniques are expected to enhance therapeutic efficacy for skeletal muscle injuries and disorders, but basic knowledge is lacking. The purpose of this study was to examine the diagnostic accuracy of ultrasound for abnormal skeletal muscle lesions, and to examine the distribution patterns of solution and cells injected into abnormal muscle lesions under ultrasound guidance. Methods: A cardiotoxin (CTX)-induced muscle injury model was used. Briefly, CTX was injected into tibialis anterior muscle in rats under ultrasound observation. First, the diagnostic accuracy of abnormal muscle lesions on ultrasound was examined by comparing ultrasound findings and histology. Next, Fast Green solution and green fluorescent protein (GFP)-labelled cells were simultaneously injected into the abnormal muscle lesions under ultrasound guidance, and their distribution was evaluated. Results: Evaluation of short-axis ultrasound images and cross-sectional histological staining showed a strong correlation (r = 0.927; p < 0.001) between the maximum muscle damage area in ultrasound and haematoxylin and eosin (H&E) staining evaluations. Histological analysis showed that ultrasound-guided injection could successfully deliver Fast Green solution around the myofibres at the site of injury. In contrast, the distribution of injected cells was very localized compared to the area stained with Fast Green. Conclusion: This experimental animal study demonstrated the potential of ultrasound to quantitatively visualize abnormalities of skeletal muscle. It also showed that ultrasound-guided injections allowed for highly accurate distribution of solution and cells in abnormal muscle tissue, but the patterns of solution and cell distribution were markedly different. Although future studies using a more clinically relevant model are necessary, these results are important findings when considering biological therapies for skeletal muscle injuries and disorders. Cite this article: Bone Joint Res 2025;14(1):33–41.